2011
DOI: 10.1007/s10482-011-9630-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic association of Paecilomyces formosus LHL10 offers thermotolerance to Cucumis sativus

Abstract: We investigated in this study the influence of an endophytic fungus, Paecilomyces formosus LHL10, on the thermotolerance of cucumber (Cucumis sativus) upon exposure to high (38°C) and low (8°C) temperature stresses. The results showed that endophyte-inoculated plants had significantly higher plant growth attributes under high-temperature stress. However, they were either low or insignificant in non-inoculated control and inoculated plants with 8°C treatments. Lower stress-promulgated water deficit and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 53 publications
3
16
1
2
Order By: Relevance
“…Growth promotion may be attributed to the ability of P. formosus LWL1 to produce multiple important secondary metabolites (Khan et al, 2012;Waqas et al, 2014). Current results are in strong agreement with the findings of Khan et al (2011), who reported the ability of the same fungus, P. formosus LHL10, to induce thermo-tolerance.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Growth promotion may be attributed to the ability of P. formosus LWL1 to produce multiple important secondary metabolites (Khan et al, 2012;Waqas et al, 2014). Current results are in strong agreement with the findings of Khan et al (2011), who reported the ability of the same fungus, P. formosus LHL10, to induce thermo-tolerance.…”
Section: Discussionsupporting
confidence: 91%
“…Plant association with phytohormones produced by endophytes has also been helpful in mitigating abiotic and biotic stresses (Khan et al, 2012;Waqas et al, 2014a;2014b). Endophytes benefit host plants in a number of ways by improving uptake of nutrients and water, water-use efficiency, endogenous hormone levels, and survivability competition without causing any harm (Khan et al, 2012). This important plantmicrobe association (Khan et al, 2012;Higgins et al, 2014;Waqas et al, 2014b) is the basis of our study.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations